Identifikasi Tindakan Cyberbullying dalam Aktivitas Online Role-Playing Berbasis Media Sosial - Subhi Nur Azmi Saleh; Lucky Nurhadiyanto (Dinasti Review, 2024)
This research focuses on identifying cyberbullying actions in social media-based online role-playing activities. This research uses a qualitative methodological approach to reveal the phenomenon of cyberbullying among roleplayers holistically and contextually. In this research, the author adopts the theories of Space Transition and Symbolic Interactionism to understand the dynamics of cyberbullying in online role-playing activities. This study found that cyberbullying can occur among roleplayers, mainly due to the lack of awareness among roleplayers and the lack of deterrence factors in cyberspace. Factors such as repressed criminal behavior in physical space, identity flexibility, anonymity, and lack of exposure to online role-playing activities also influence roleplayers' behavior, including criminal behavior such as cyberbullying. This research is expected to provide deeper insights into how cyberbullying acts in online role-playing activities and how to take steps to reduce the risk of engaging in negative behaviors in the virtual realm.